Functional-coefficient spatial Durbin models with nonparametric spatial weights: An application to economic growth - Mustafa Koroglu; Yiguo Sun (Econometrics, 2016)
This paper considers a functional-coefficient spatial Durbin model with nonparametric spatial weights. Applying the series approximation method, we estimate the unknown functional coefficients and spatial weighting functions via a nonparametric two-stage least squares (or 2SLS) estimation method. To further improve estimation accuracy, we also construct a second-step estimator of the unknown functional coefficients by a local linear regression approach. Some Monte Carlo simulation results are reported to assess the finite sample performance of our proposed estimators. We then apply the proposed model to re-examine national economic growth by augmenting the conventional Solow economic growth convergence model with unknown spatial interactive structures of the national economy, as well as country-specific Solow parameters, where the spatial weighting functions and Solow parameters are allowed to be a function of geographical distance and the countries' openness to trade, respectively.
Keywords: C14; C21; O47; 330; functional coefficients; local linear regression; nonparametric 2SLS estimator; series estimator; Solow economic growth convergence model; spatial Durbin model